Die demokratische Schließung. Zum Verhältnis von Alterität und liberaler Demokratie in juridico-politischen Diskursen, sozialen Performanzen und räumlichen Manifestationen - Gebhardt, Mareike (Grenze und Demokratie. Ein Spannungsverhältnis, 2017)

Gegenwärtig sein. Hannah Arendt neu denken - Gebhardt, Mareike; Morgernstern, Kathrin; Herb, Karlfriedrich (Raum und Zeit. Denkformen des Politischen bei Hannah Arendt, 2014)

Grenzverschiebungen. Überschreitung als demokratische Praxis - Gebhardt, Mareike (Die Grenzen der Demokratie. Gegenwartsdiagnosen zwischen Politik und Recht, 2017)

Ökonomien der Un/Sichtbarkeit – Spektakel der Souveränität. Die Figur des Ausnahmezustands im Angesicht des Anderen - Gebhardt, Mareike (Ausnahmezustand. Theoriegeschichte - Anwendungen - Perspektiven, 2017)

On Dreaming Public. Between the Irony of the Self and the Recognition of the Other - Gebhardt, Mareike (Narrative, Dreams, Imagination. Israeli and German Youth imagine their Futures, 2013)

Pest‘ und ‚Lepra‘. Mechanismen der Un/Sichtbarkeit der europäischen Asylpolitik - Gebhardt, Mareike (Foucault und das Politische. Transdisziplinäre Impulse für die politische Theorie der Gegenwart, 2019)

Politische Pluralität und philosophischer Wahrheitsanspruch. Hannah Arendt, Jürgen Habermas und Richard Rorty zwischen Kommunikation und Narrativität - Gebhardt, Mareike (Narrative Formen der Politik, 2014)

Politisches Handeln in der postmodernen Konstellation. Kritische Demokratietheorie nach Hannah Arendt und Jürgen Habermas - Gebhardt, Mareike (Nomos, 2014)

Postmoderne und Pluralität. Ein demokratischer Aufbruch ins 21. Jahrhundert - Gebhardt, Mareike (2014)

Raum und Zeit. Denkformen des Politischen bei Hannah Arendt - Gebhardt, Mareike; Herb, Karlfriedrich; Morgernstern, Kathrin (Campus, 2014)

The populist moment: affective orders, protest, and politics of belonging - Gebhardt, Mareike (Distinktion, 2019)
Populism of the twenty-first century, the paper argues, emerges from the aloofness of liberal democracy’s sober regimes of rationality. This results in political movements that are explicitly affective in their strategies, both on the right and the left of the political spectrum. However, while policy research claims that left- and right-wing populism ‘look alike’ (isomorphia), the paper shows that there is only one populist logic that exceeds demarcations of ‘left’ or ‘right’. Therefore, it introduces the concept of the populist moment to describe the structure of the populist logic that is shared by a variety of protest movements. As a feminist intervention in the field of populism studies, the paper, finally, discusses how Mouffe’s political theory conflates ‘left populism’ and radical democracy. In reference to Ranciére’s and Lorey’s conceptualizations of radical democracy the paper portrays how to democratize democracy beyond Mouffe’s hegemony theory.
CRIS-Team Scopus Importer:2019-08-30
Keywords: affect; citizenship; Populism; protest; radical democracy; transnationality

Verprechen, Vergessen, Vereinsamen. Hannah Arendt und Friedrich Nietzsche als Denker politischer Zeitlichkeit - Gebhardt, Mareike (Raum und Zeit. Denkformen des Politischen bei Hannah Arendt, 2014)

Von Göttern und Engeln. Die Republik zwischen Ideal und Utopie bei Immanuel Kant und Jean-Jacques Rousseau - Gebhardt, Mareike (Rousseaus Zauber. Lesarten der Politischen Philosophie, 2012)

Zeitlichkeit und Materialität. Interdisziplinäre Perspektiven auf Theorien und Phänomene der Präsenz - Kirchmann, Kay; Engel, Juliane; Gebhardt, Mareike (2019)